Double layered dielectric elastomer by vapor encapsulation casting for highly deformable and strongly adhesive triboelectric materials. (August 2019) - Xu, Hai Bo; Kim, Jeong Hun; Kim, Sangtae; Hwang, Hee Jae; Maurya, Deepam; Choi, Dukhyun; Kang, Chong-Yun; Song, Hyun-Cheol
Abstract: Triboelectric generators (TEG), based on contact electrification and electro-static induction, has received a significant attention because of their numerous applications. To improve the electrified surface charge density in TEG, increasing the surface area of dielectric materials or forming internal hollow structures are typically employed to increase capacitance. However, the fabrication processes of such structures are complex and time-consuming. Here, we provide a facile and cost-effective synthesis method for the porous PDMS based TEG via a novel vapor encapsulation casting (VEC). The double dielectric layer composed of the porous and dense PDMS layers are formed in-site through VEC. The thickness and the thickness ratio of the double dielectric layer can be precisely controlled by adjusting the uncured PDMS thickness and vapor penetration depth. The double dielectric layer TEG (DTEG) exhibits the improved harvesting performance because the porous dielectric layer increases the capacitance and compressibility, while the dense layer passivates the fully open pores which reduce the charging surface area as completely opening through the dielectric layer without contacting the bottom electrode. We obtain the maximum output voltage of 345 V and short circuit current of 3 μA/cm 2 from DTEG having 0.95 porous thickness ratio, resulting 330% enhancement in the power output as compared to the dense PDMS based TEG. We further investigate the performance of DTEG under various operating conditions. We also demonstrate the operation of Bluetooth distance/temperature sensors using capacitors charged by DTEG. Graphical abstract: Image 1 Highlights: TEG based on the double dielectric layer composed of the sponge-like porous and flat dense elastomer is demonstrated. Facile and affordable synthesis method for the porous PDMS is provided via the novel vapor encapsulation casting. Highly deformable porous PDMS effectively enhances its capacitance under a pressure. Flat dense second layer of PDMS reduces the device impedance and improves the contact interface with an electrode.